Parametric - Nature Obsession - Dr.Aref Maksoud, Hala Sahall, Mohammad Massarweh, Duha Taher, Marwa Al Nahlawi, Lama Maher, Sana Al Khaled, Ahmad Auday (International Journal of Advanced Science and Technology, 2020)
This paper examines the basic application and usage of wood construction in landscape and tests the influence of the material’s behavior on the structure of parametric elements. Over the years, nature has inspired artists and designers and is being reflected in many forms starting from wall paintings up to building facades. With the development in technology, it is important to understand how to use computer programs to portrait the elements of nature and integrate them in the design process. Designers favor parametric design due to its flexibility and its simplification to complex ideas by providing automated solutions, which led to the wide use of parametric design and the use of wooden materials in urban landscaping. The final exercise of the Parametric Design course at The University of Sharjah / Department of Architectural Engineering was to evaluate the students’ understanding of the course learning outcomes and the skills developed, a system was to be designed to respond with material, function and location. For the sake of understanding the fabrication process, the students were required to fabricate their proposals using simple materials: Structure + Skin + Materials + Forces = System. Parametric algorithm was created to vary the fluidity of the shape, and optimization of material used. Benches and tables are CNC cut, fabricated out of 18mm thick wood slices. The Delonesk Table is one of the final built results that follows the strategy of non-overlapping yet contiguous triangles from a set of points. The Delaunay Triangulation is used in furniture production. Another built project by the students The RAK Coffee Table is inspired by the beauty that can be found in the United Arab Emirates. Extracted from the topographic map of the famous mountainous region of Jebel Jais and its roundabouts in Ras Al-Khaimah